THE REPRESENTATION OF LIBERAL FEMINISM IN A WOMAN IS NO MAN BY ETAF RUM - Wulandari, Mega Dwi; Supiastutik, Supiastutik; Pujiati, Hat (LPPM STKIP PGRI Bandar Lampung, 2019)
This study discusses liberal feminism in 21st century in America. Liberal feminism. The representation of liberal feminism in A Woman is No Man explains how powerful is the feminism movement in encouraging Arab woman in Arab-American society. The representation of liberal feminism in A Woman is No Man is depicted through female characters’s struggle in getting the equal right with men. The narratives and the dialogues of the novel construct the discourse of liberal feminism where Arab women are considered as inferior and Arab men are considered as a superior. However, the liberal feminism is showed through the main female characters’ struggle to get the same equal right with men in the novel. According to this reason, Stuart Hall's representation theory and discursive approach by Michel Foucault are applied as the main tool to analyze the problems. Betty Frieddan’s Feminine Mystique is utilized as the supporting theory to analyze the liberal feminism in the novel. The results of this study shows that the idea of Arab men is superior, Arab women are inferior become a common knowledge and general agreement among society.